2017
DOI: 10.1016/j.drugalcdep.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with alcohol use prior to and during pregnancy among HIV-infected pregnant women in Cape Town, South Africa

Abstract: Introduction Alcohol use during pregnancy is prevalent in South Africa, but there are few prospectively-collected data exploring patterns of consumption among HIV-infected women, which may be important to improve maternal and child health outcomes. We examined patterns of and factors associated with alcohol use prior to and during pregnancy among HIV-infected pregnant women in Cape Town, South Africa. Methods Participants were enrolled when entering antenatal care at a large primary care clinic, and alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
10
2
Order By: Relevance
“…Literature investigating the relationship between HIV-related stigma and alcohol use among PLWH remains limited. A study of PLWH in Russia found a positive relationship between stigma and alcohol dependence (31) while, in contrast, a study of PLWH in South Africa did not find a significant relationship between HIV-related stigma and alcohol use (16). The relationship between problem drinking and internalized HIV-related stigma identified in the current study remains unclear.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Literature investigating the relationship between HIV-related stigma and alcohol use among PLWH remains limited. A study of PLWH in Russia found a positive relationship between stigma and alcohol dependence (31) while, in contrast, a study of PLWH in South Africa did not find a significant relationship between HIV-related stigma and alcohol use (16). The relationship between problem drinking and internalized HIV-related stigma identified in the current study remains unclear.…”
Section: Discussioncontrasting
confidence: 92%
“…Despite the consistent relationship between alcohol abuse and poor HIV treatment outcomes, psychosocial factors associated with alcohol abuse among PLWH remain poorly understood, including in sub-Saharan Africa, where the majority of PLWH reside. Among extant research with PLWH in South Africa, high risk drinking has been associated with depressive symptoms (16). Little is known about the extent to which psychosocial factors associated with problem drinking differ by gender among PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…Unplanned/unwanted pregnancy Urban et al, 2016;Fletcher et al, 2018 3 Violence Louw et al, 2011;O'Connor et al, 2011;Eaton et al, 2012;Culley et al, 2013;Choi et al, 2014;Cloete and Ramugondo, 2015;Onah et al, 2016;Brittain et al, 2017;Davis et al, 2017;Wong et al, 2017;Fletcher et al, 2018;Petersen et al, 2018 12 Trauma Cloete and Ramugondo, 2015;Urban et al, 2016;Fletcher et al, 2018;Myers et al, 2018 4 Mental health Morojele et al, 2010;Louw et al, 2011;O'Connor et al, 2011;Desmond et al, 2012;Cloete and Ramugondo, 2015;Onah et al, 2016;Davis et al, 2017;Wong et al, 2017;Fletcher et al, 2018;Myers et al, 2018;Peltzer and Pengpid, 2019 12 Drinking culture May et al, 2005;May et al, 2008;Morojele et al, 2010;Louw et al, 2011;Watt et al, , 2016Cloete and Ramugondo, 2015;Petersen-Williams et al, 2018 7 Alcohol availability Morojele et al, 2010 1 Previous alcohol exposure Morojele et al, 2010;Choi et al, 2014 2 Opportunities for leisure Cloete and Ramugondo, 2015;…”
Section: Studies Which Mention Theme Number Of Studiesmentioning
confidence: 99%
“…A recent report by World Health Organization (WHO) found that roughly one-third (34%) of women reported having engaged in this behavior in the month preceding the survey (3) while another study found that a similar proportion of women (32%) reportedly engage in binge drinking on a weekly basis (4). Alcohol use is also common among pregnant women in Cape Town (5)(6)(7)(8). Prior work among pregnant women in this setting found that 29% reported alcohol use during pregnancy (9), an estimate that is likely biased due to underreporting/social desirability bias (10).…”
Section: Introductionmentioning
confidence: 99%